Escapist’s perspective model for promoting road traffic decongestion and safety in Nigerian megacities. - Onumbu, Chime Ishmael (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
Nigeria is a fast-developing country with its multifarious megacities, which pose serious road traffic congestion. This study aimed to ascertain the relevance of the escapist's perspective model implementation in the promotion of road traffic decongestion and safety in Nigerian megacities. A descriptive survey design and multi-procedural approach were used in the study to arrive at the design, the population and the sample size. On the whole, 2,497 was the population while 250, comprising 158 males and 92 females formed the sample size. The validity was contrived and a reliability co-efficient of 0.72 was obtained. Using the statistical package for social sciences (SPSS), the received data were analyzed for the mean, standard deviation in the research question, and Z-value test at 0.05 level of significance hypothesis test. The result showed that all the respondents perceived that the escapist's perspective model which involves the use of the 4 D's and their various items is relevant in the promotion of road traffic decongestion and safety in Nigerian megacities. Also, it was recommended that various governments in Nigeria should adopt the 4D's in their bid to eradicate traffic congestion on our roads and promote road traffic safety in Nigerian mega cities. Also, this study recommended that promoting road traffic decongestion aids in improving the economic and public health standards of society and good governance.